When the Boss Comes to Town: The Effects of Headquarters' Visits on Facility-Level Misconduct - Heese, Jonas; Pérez-Cavazos, Gerardo (The Accounting Review, 2020)
ABSTRACT We study the effects of visits by headquarters' managers on facility-level misconduct. These visits are central to monitoring, but are difficult to observe for a large sample of firms. We use the staggered introduction of airline routes to identify exogenous reductions in travel time between headquarters and facilities as our measure of visits and test whether the reductions affect misconduct. We find that for the at-risk sample, travel-time reductions decrease the number of violations by 2 percent and penalties by 23.4 percent, suggesting that management focuses on reducing costlier violations, as opposed to simply reducing the number of violations. These effects are concentrated in firms with weaker control systems, suggesting that strong controls can act as substitutes for visits. Furthermore, the introduction of broadband internet attenuates, but does not eliminate the effect of reductions on misconduct. Finally, we find that reductions result in greater misconduct when firms are subject to performance pressure. JEL Classifications: M40; M41; M46.